SIMULATION OF TSUNAMI WAVE PROPAGATION AND RUN-UP AT PANGANDARAN BAY, WEST JAVA - Petrus Subardjo; Siddhi Saputro; Sofia Alma Aeda (International Journal of Marine and Aquatic Resource Conservation and Co-existence, 2017)
ABSTRACTPangandaran is an area located in Southern of Java Island, which dealing with the Indian Ocean. In the Indian Ocean, there is a subduction zone between the plates that can cause earthquakes and tsunami, as an example earthquakes and tsunami in Pangandaran (2006). The earthquake and tsunami that have occurred in an area, potentially happen again in the future. The purpose of the research is to determine the height of tsunami, tsunami time travel and tsunami wave run-up. This research was conducted on December 29th to 30th, 2015 in Pangandaran Bay with coordinates between 108°20’00” E - 108°47’00” E and 7°36’00” S - 7°48’00” S. The method used is quantitative method and the method that has been used to determine research location is purposive sampling. The data used are the source of earthquake faults, bathymetry data, and slope the beach. Data modeled using COMCOT v1.7 software to determine the height of tsunami and tsunami time travel. The height of tsunami wave by simulation model used to determine tsunami wave run-up. The simulation result known tsunami wave height range from 2 to 9 meters with run-up between 0 to 510 meters. The highest tsunami wave at observation point 3 and the lowest at observation point 1. The highest run-up tsunami at observation point 3 and the lowest at observation point 6. Time required for tsunami waves reach land between 39 to 48 minutes. Based on the result can be concluded that the highest tsunami wave located in sloping morphology, while the lowest tsunami located in high area or behind the cape area. Key words: The tsunami, Pangandaran, Comcot, Run – up